Results of definitive radiotherapy with concurrent chemotherapy for maxillary sinus carcinomas with neck lymph node metastasis. (7th December 2020) - Abe, Takanori; Saito, Satoshi; Iino, Misaki; Aoshika, Tomomi; Ryuno, Yasuhiro; Ohta, Tomohiro; Igari, Mitsunobu; Hirai, Ryuta; Kumazaki, Yu; Ebihara, Yasuhiro; Nakahira, Mitsuhiko; Sugasawa, Masashi; et al.
Abstract: The purpose of this study was to describe the results of definitive radiotherapy (RT) with concurrent chemotherapy for maxillary sinus carcinomas (MSCs) with neck lymph node metastasis to clarify its limitation. Local control (LC), progression-free survival (PFS) and overall survival (OS) rates were calculated using the Kaplan–Meier method and were compared between subgroups using the log rank test. Toxicity was classified using common terminology criteria of adverse events version 5.0. Eighteen patients with inoperable MSC with neck lymph node metastasis including 12 men and 6 women with a median age of 67 years were analyzed. The histologic diagnoses were as follows: 16 patients had squamous cell carcinomas and 2 had other histology. Four patients had stage T3 MSC, 6 had T4a and 8 had T4b. Among 18 patients, 7 received concurrent systemic chemotherapy and 11 received selective arterial chemo-infusion. The median follow-up period was 17 months. The 2-year LC, PFS and OS rates for the entire cohort were 34, 31 and 46%, respectively. No significant differences were observed for LC, PFS and OS rates between systemic chemotherapy and selective arterial chemo-infusion cohorts. Grade 3 or higher acute toxicity, including both non-hematological and hematological, was observed in nine patients (50%), while no grade 3 or higher late toxicity was observed. In conclusion, we described the results of definitive RT for MSCs with neck lymph node metastasis. Local recurrence of primary tumor was a frequent pattern of failure and it should be addressed in future study.